Revitalization of Mushroom Cultivation as a Living Laboratory for Family Economic Empowerment and Sustainable Entrepreneurial Construction for STIS Darul Falah Cermee Bondowoso Students - Mustaqim Makki; Andi Susanto; Achmad Nur; Subairi (Al Busyro : Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to examine the revitalization of mushroom cultivation as a living laboratory for family economic empowerment and sustainable entrepreneurship development for STIS Darul Falah Cermee Bondowoso students. The problems identified include low productivity of mushroom cultivation, limitations in product processing and marketing, and lack of student experience in agribusiness-based entrepreneurship. This study uses the Asset-Based Community Development (ABCD) approach, which emphasizes the use of local assets, such as land and community skills. Implementation is carried out through technical training in mushroom cultivation, development of processed products, as well as the application of product packaging and halal labeling. The results of the study showed an increase in the quality and quantity of mushroom production, a more empowered family income, and an increase in students' entrepreneurial skills. The program creates a sustainable and applicable model of community service, with recommendations for further development in product innovation and evaluation of long-term impacts.